(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article analyzes existing and potential future problems in the field of water resources in Uzbekistan. The article focuses on the study of the factors that influence policy development in the area of efficient use of water resources use in Uzbekistan. The article also focuses on the issues of rational use of water resources in drinking water supply and irrigated agriculture in Uzbekistan, as well as the advantages of water saving technologies and their solutions.We attempt to outlines the state of water resources in the country, chemical and biological analysis of water resources, highlighting the most important issues and some recommendations for the development of water conservation technologies.